2022
DOI: 10.3389/fonc.2022.904644
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab monotherapy for untreated PD-L1-Positive non-small cell lung cancer in the elderly or those with poor performance status: A prospective observational study

Abstract: ObjectivesWe investigated the efficacy and safety of pembrolizumab monotherapy as first-line treatment for poor Eastern Cooperative Oncology Group performance status (PS) and elderly patients with programmed cell death-ligand 1 (PD-L1)-positive advanced non-small cell lung cancer (NSCLC). We also investigated clinical prognostic factors for the efficacy of pembrolizumab monotherapy, based on patient characteristics.Materials and methodsIn this prospective observational study, PS-2 and elderly NSCLC patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…After a median follow-up of 34 months, the median real-world time on first-line pembrolizumab monotherapy was 7.4 (6.3–8.1) months for the entire cohort but only 2.1 (1.4–2.8) months for the 237 patients with ECOG PS = 2 12 . The same effect was also observed in a multicenter Japanese study on 40 elderly patients (median age 78.5 y) and/or ECOG PS = 2 (40%); 9 the objective response rate was 40.5% and the disease-control rate was 62%. After a median (95% CI) follow-up of 9.5 (0.3–27.1) months, median PFS and OS for patients ≥75 years old were, respectively, 5.3 (2.9–9.4) and 11.6 (7.4–18.1) months, with respective durations for those with ECOG PS = 2 of 4.4 (0.9–14.4) and 11.6 (1.4–NR) months.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…After a median follow-up of 34 months, the median real-world time on first-line pembrolizumab monotherapy was 7.4 (6.3–8.1) months for the entire cohort but only 2.1 (1.4–2.8) months for the 237 patients with ECOG PS = 2 12 . The same effect was also observed in a multicenter Japanese study on 40 elderly patients (median age 78.5 y) and/or ECOG PS = 2 (40%); 9 the objective response rate was 40.5% and the disease-control rate was 62%. After a median (95% CI) follow-up of 9.5 (0.3–27.1) months, median PFS and OS for patients ≥75 years old were, respectively, 5.3 (2.9–9.4) and 11.6 (7.4–18.1) months, with respective durations for those with ECOG PS = 2 of 4.4 (0.9–14.4) and 11.6 (1.4–NR) months.…”
Section: Discussionsupporting
confidence: 66%
“…According to the findings of those 2 studies, ECOG PS ≥2 was an independent factor associated with poorer OS 3,4 . That observation was echoed in other reports 5–12 . The results of a prospective, observational study on 40 patients with ECOG PS = 2 or ≥75 years old, with ≥1% PD-L1 expression on their aNSCLC cells showed that median (95% CI) OS on first-line pembrolizumab lasted 11.6 (1.4–NR) months for patients with ECOG PS = 2 and 11.6 (7.4–18.1) months for the elderly 9 .…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…However, whether ICI plus chemotherapy is effective and safe for frail patients, such as older patients or those with poor ECOG PS, remains uncertain . In contrast, several previous studies have shown the efficacy and safety of pembrolizumab monotherapy in these frail populations; therefore, pembrolizumab monotherapy may be a more reasonable treatment option than ICI plus chemotherapy for frail patients with NSCLC with high PD-L1 TPS in a clinical setting. Considering the treatment strategy for these clinical patients, we should recognize that PPI use may be negatively associated with the treatment outcome of ICI monotherapy.…”
Section: Discussionmentioning
confidence: 99%